Effects of 4-week circuit strength combined with blood flow restriction training on muscle status and performance in Taekwondo athletes - Li, W.; Gao, Z.; Liu, Y.; Wang, J. (Journal of Human Sport & Exercise, 2024)
This study explored the effects of a 4-week circuit strength training with blood flow restriction on Taekwondo athletes. Six male athletes (age 20.6 ± 1.85, height 184.3 ± 7.63 cm, training duration 7.5 ± 2.07 years) were assessed for explosive strength, muscle recruitment, and sport-specific skills. The regimen encompassed evaluations of lower limb power, Isokinetic strength, force via electronic kicks, and Tensiomyography (TMG) measurements pre-and post-training. Outcomes revealed enhanced jumping abilities, improved knee muscles, and superior kicking skills. There was a notable increase in muscle fibre recruitment and a shift towards type II muscle fibres. Medial thigh muscle displacement showed a positive correlation with jump duration, while lateral thigh muscles indicated a connection with kick numbers. The regimen notably improved explosive power, muscle fibre distribution, and reduced muscle contraction times. Yet, no significant changes in lower limb bilateral symmetry or the link between TMG parameters and athletic prowess were observed.